Pulmonary Lymphangioleiomyomatosis originates in the pleural mesothelial cell population. (August 2020) - Clements, D.; Miller, S.; Johnson, S.R.
Abstract: Lymphangioleiomyomatosis (LAM) is a cystic lung disease mainly affecting women, in which degradation of the lung parenchyma is associated with a cell of unknown provenance, known as a LAM cell. LAM cells carry TSC2 mutations and can be identified in the lung parenchyma by their expression of both smooth muscle actin and antigens characteristic of melanocytes and melanocytic tumors. The nature of the cell-of-origin of LAM is controversial, and despite continued research effort remains elusive. Further, it has not been possible to culture pulmonary LAM cells in vitro, and current research relies on cells and animal models which may not recapitulate all features of the disease. We noted aberrant expression of melanoma antigens in pleural mesothelial cells in lung tissue from LAM patients, indicating that these cells could be the precursors of parenchymal LAM cells. We hypothesise that loss of tuberin function following TSC2 mutation in the mesothelial cell lineage gives rise to the cell-of-origin of pulmonary LAM (P-LAM), and of other associated conditions commonly noted in LAM patients. The unique properties of mesothelial cells provide a straightforward explanation of the diverse presentation of LAM.